Going Once, Going Twice, Reported! - Jeroen Hinloopen; Sander Onderstal (Tinbergen Institute, 2009)
We experimentally examine the effectiveness of antitrust policies against bidding rings in theEnglish auction (EN) and the first-price sealed-bid auction (FP). We consider both traditionalantitrust policy (without a leniency program) and modern antitrust policy (with a leniencyprogram). In EN, neither antitrust policy has a significant effect on cartel deterrence, cartelstability, cartel recidivism, and winning bids. In FP, traditional antitrust policy deters cartelformation, destabilizes cartels, reduces the probability that a cartel re-establishes, and reduces theaverage winning bid. In contrast, while a leniency program has no additional effect on cartelformation or cartel recidivism, it makes cartels more stable and reduces the winning cartel bid.
Keywords: C92; D44; L41; 330; Antitrust policy; Leniency Programs; English Auction; First-Price Sealed-Bid Auction; Laboratory Experiments; Straffreiheit; Kartell; Auktionstheorie; Test